Makna di Balik Legenda “Gunung Tangkuban Parahu”: Suatu Kajian Semiotik - Munandar, Ilham; Indira, Dian (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2021)
In this research,  the meaning of the legend  of “Gunung Tangkuban Parahu” is analyzed. The problem in this research is to investigate how denotation, connotation, as well as myth in the legend of “Gunung Tangkuban Parahu”. The objective of this research is to know denotation meaning as signifier, connotation meaning as signifier, as well as myth in the legend of “Gunung Tangkuban Parahu”. Roland Barthes’s semiotics theory is used in this research which identified two orders of signification,  the first order signification is the language aspect, and the second one is the mythical aspect. The method  used in this research is qualitative research method. Based on the result, it is found the denotation of Gunung Tangkuban Parahu” as a signifier, the connotation of Gunung Tangkuban Parahu as a signifier of forbidden love between mom and son, and the myth of Gunung Tangkuban Parahu which is formed from an upside down boat.